Analysis of Disease Patterns in Bombana District for the Period 2021-2023: A Case Study in the Working Areas of the Lantari Jaya and Tontonunu Subdistrict Community Health Centers - Sitti Nur Afridasari Titi afrida; Siti Aisyah Karimuna; Wa Ode Hikmah Noor Shafar Nafiu (Journal of Epidemiology and Health Science, 2026)
Background: Indonesia has a double burden of disease, which means that both infectious and non-communicable diseases are happening at the same time. Differences in sanitation, the environment, and availability to health care services lead to different patterns of disease in different areas, such as Bombana District. Objective: This study aims to examine infectious and non-infectious disease patterns (double burden), create risks in society and the environment (sanitation and early marriage/poverty), and see how health resources suppress disease in Bombana District, contrasting Lantari Jaya and Tontonunu subdistricts (2021–2023). Methods: The research utilized a learning approach of issues that explains and describes based on previous evidence from annual Community Health Centers (Lomba Kasih and Tontonunu) reports, health facilities, health workers, and sanitation quality reports during implementation. Side-by-side information was compared to determine changes and differences in disease transmission, and services' quality. Sources of information were the Central Statistics Agency and Health Profile of Bombana Health Office in 2023. Results: Disease frequency indicated the highest lung infection rates were in Lantari Jaya (most significant) and non-communicable diseases (NCDs), especially high blood pressure and diabetes, had the fastest growth. High blood pressure and possible lung TB became the most common in Tontonunu in 2023; they were most common for lung infections before. Great variations were found in maintaining good sanitation: Lantari Jaya was 95.04%, and none but Tontonunu came close to 67.33%, which was still able to spread disease from the environment, like diarrhea, in Tontonunu. Conclusion: Double disease issue for Bombana District aggravated by unequal access to sanitation facilities and differing degrees of each subdistrict fostering health. Sanitation was first to be improved in Tontonunu, deployment of PTM Posbindu, and combined reproductive health education programs to curb early marriage as a preventive measure against stunting in the long term. Keywords: Disease Patterns, Health Facilities, Adequate Sanitation Health Workers, Public Health Center